Development of a pc-based tank model real-time flood forecasting system - Cheok, Hou Seng (2005)
The Upper Klang catchment has been under-going rapid development which instigated many flash flood occurrences within the catchment, especially at the Kuala Lumpur City. A reliable and timely flood forecasting system is necessary to provide early warning to minimize the destruction caused by flash floods. Utilizing the publicly available online hydrological data combined with the most recent programming technologies, a PC-based a real-time flood forecasting system is developed for this purpose. The Tank Model is used as the hydrological model to simulate the catchment discharge while the Standard Step Method applied as the hydraulic model to simulate the water level profile of Klang River starting from the confluence of Klang and Ampang River to Jambatan Tun Perak. Integration of both models into a complete real-time hydro-dynamic flood forecasting system is programmed using the Microsoft Excel and Visual Basic For Application. Calibration and Verification of the model has proven that forecast generated by the system is highly reliable with an average Model Efficiency of 89.37% and a Mean Absolute Error of 0.23m. The system acquires real-time hydrological data from the Infobanjir server maintained by Department of Irrigation and Drainage Malaysia at 5 minutes intervals and is therefore able to provide a reliable and timely warning at 40 minutes before the flood peak reaches the city center.